Investigation of the Effects of Phenolic Extracts Obtained from Agro-Industrial Food Wastes on Gelatin Modification - Demircan, Huseyin; Oral, Rasim A.; Toker, Omer S.; Palabiyik, Ibrahim (AMER CHEMICAL SOC, 2024)
In this study, modified bovine gelatin was produced using the alkaline technique with four different oxidized agro-industrial food waste (pomegranate peel (PP), grape pomace and seed (GP), black tea (BT), and green tea (GT)) phenolic extracts (AFWEs) at three different concentrations (1, 3, and 5% based on dry gelatin). The effect of waste type and concentration on the textural, rheological, emulsifying, foaming, swelling, and color properties of gelatin, as well as its total phenolic content and antioxidant activity, was investigated. Significant improvement in gel strength, thermal stability, and gelation rate of gelatin was achieved by modification with oxidized agro-industrial waste extracts. Compared to the control sample, 46.24% higher bloom strength in the GT5 sample, 5.29 and 6.01 degrees C higher gelling and melting temperatures in the PP5 sample, respectively, and 85.70% lower t(model) value in the GT3 sample were observed. Additionally, the total phenolic content, antioxidant activity, foam, and emulsion properties of the modified gels increased significantly. This study revealed that gelatins with improved technological and functional properties can be produced by using oxidized phenolic extracts obtained from agricultural industrial food wastes as cross-linking agents in the modification of gelatin.
Keywords: SKIN GELATIN; FISH GELATIN; EMULSIFYING PROPERTIES; ANTIOXIDATIVE ACTIVITY; RHEOLOGICAL PROPERTIES; ETHANOLIC EXTRACT; GEL PROPERTIES; TANNIC-ACID; PROTEIN; TEXTURE; Chemistry